Evaluation of a Web-based tailored intervention (TAVIE en santé) to support people living with HIV in the adoption of health promoting behaviours: an online randomized controlled trial protocol. (December 2015) - Côté, José; Cossette, Sylvie; Ramirez-Garcia, Pilar; Pokomandy, Alexandra; Worthington, Catherine; Gagnon, Marie-Pierre; Auger, Patricia; Boudreau, François; Miranda, Joyal; Guéhéneuc, Yann-Gaël; Tremblay, Cécile
Abstract Background Long-term use of antiretroviral therapy, normal aging, and presence of certain risk factors are associated with metabolic disorders that predispose persons living with HIV to diabetes and cardiovascular diseases. The emergence and progression of these disorders can be prevented by adopting healthy behaviours. Based on the theory of planned behaviour, the Web-based tailored interventionTAVIE en santé was developed. The aim of this study is to evaluate the effectiveness ofTAVIE en santé in order to support people living with HIV in the adoption of health promoting behaviours. Methods/Design An online randomized controlled trial with parallel-groups will be conducted across Canada. To participate in this study, people living with HIV must be: ≥ 18 years, able to read/understand French or English, have access to the Internet. A convenience sample of 750 participants will be randomly assigned either to an experimental group (TAVIE en santé, n = 375) or to a control group (websites, n = 375) (1:1 allocation ratio). TheTAVIE en santé intervention is composed of seven interactive computer sessions, lasting between 5 and 10 min. The sessions, hosted by a virtual nurse, aim to develop and strengthen skills required for behaviour change. The control group will receive a validated list of five predetermined conventional health-related Websites. The adoption of health behaviour (smoking cessation or physical activity or healthy eating) is the principal outcome. Cognitions (intention, attitude, perceived behavioral control) are the secondary outcomes. Health indicators will also be assessed. All outcomes will be measured with a self-administered online questionnaire and collected three times: at baseline, 3 and 6 months after. The principal analyses will focus on differences between the two trial groups using Intention-to-Treat analysis. Discussion This study will yield new results about the efficacy of Web-based tailored health behaviours change interventions in the context of chronic disease. TheTAVIE en santé intervention could constitute an accessible complementary service in support of existing specialized services to support people living with HIV adopt health behaviors. Trial registration NCT02378766, assigned on March 3th 2015.